ICT INTEGRATION IN EDUCATION: THE CASE OF SECONDARY SCHOOLS IN KERALA - Anil, Arunima; Jayakumar, M S (PEOPLE: International Journal of Social Sciences, 2019)
The quality of education in rural areas has not risen to the expected standard due to lack of access, inadequate infrastructure, poor connectivity of ICT, and insufficient number of teachers, etc. This empirical study aims at finding out the factors influencing successful ICT integration in rural schools with special focus on the availability of ICT infrastructure, extent of ICT utilization in classrooms and the barriers encountered in its effective usage. The findings indicate that ICT infrastructure is inadequate and its use in teaching and learning were found to be minimal and has not brought about much improvement. Underutilization of the technology has resulted in lowering the digital competency of the students. Frequent utilization of smart-classrooms along with a strong ICT infrastructure and their integration into teaching activities can play a significant role in facilitating digital education in rural schools.